Risk mapping for better governance in biobanking: the case of biobank.cy - Akyüz, Kaya; Goisauf, Melanie; Martin, Gillian M.; Mayrhofer, Michaela Th.; Antoniou, Stella; Charalambidou, Georgia; Deltas, Constantinos; Malatras, Apostolos; Papagregoriou, Gregory; Stefanou, Charalambos; Voutounou, Mariel (Frontiers in Genetics, 2024)
Introduction Risk governance is central for the successful and ethical operation of biobanks and the continued social license for being custodians of samples and data. Risks in biobanking are often framed as risks for participants, whereas the biobank’s risks are often considered as technical ones. Risk governance relies on identifying, assessing, mitigating and communicating all risks based on technical and standardized procedures. However, within such processes, biobank staff are often involved tangentially. In this study, the aim has been to conduct a risk mapping exercise bringing biobank staff as key actors into the process, making better sense of emerging structure of biobanks. Methods Based on the qualitative research method of situational analysis as well as the card-based discussion and stakeholder engagement processes, risk mapping was conducted at the biobank setting as an interactive engagement exercise. The analyzed material comprises mainly of moderated group discussions. Results The findings from the risk mapping activity are framed through an organismic metaphor: the biobank as a growing, living organism in a changing environment, where trust and sustainability are cross-cutting elements in making sense of the risks. Focusing on the situatedness of the dynamics within biobanking activity highlights the importance of prioritizing relations at the core of risk governance and promoting ethicality in the biobanking process by expanding the repertoire of considered risks. Conclusions With the organismic metaphor, the research brings the diverse group of biobank staff to the central stage for risk governance, highlighting how accounting for such diversity and interdependencies at the biobank setting is a prerequisite for an adaptive risk governance.